168 Effects of Increasing Dietary Standardized Ileal Digestible Lysine Levels on Growth Performance of 12- to 26-kg Pigs Sired by High Index Boars - Vier, Carine M (J Anim Sci, 2021)
Our objective was to determine the effects of increasing dietary standardized ileal digestible (SID) lysine (Lys) on the growth performance of late nursery pigs. A total of 1,125 pigs (PIC 337×Camborough, initially 12.0±0.66 kg) were used in a 21-d study. The pigs used in the study were sired by boars ranked in the top 15% of a selected PIC elite boar stud based on index. Pens of pigs were blocked by body weight and randomly allotted to 1 of 5 treatments containing 0.95, 1.10, 1.20, 1.35, and 1.50% of SID Lys. Diets were corn-soybean meal-based and contained 2,480 Kcal of NE/kg. Treatments were achieved with increasing feed-grade amino acids. There were 9 mixed gender pens per treatment and 25 pigs per pen. Data were analyzed using generalized linear and nonlinear mixed models with pen as the experimental unit. Competing models included linear, quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic (BLQ). Increasing SID Lys concentration improved average daily gain (ADG, linear, P < 0.001) and gain to feed ratio (G:F, quadratic, P = 0.011). The best-fitting models for ADG were QP and BLL. The QP model estimated the maximum ADG at 1.43% (95% CI: 1.12 to >1.50%), with 99% of maximum ADG achieved at 1.27%. The BLL plateau was estimated at 1.31% (95%CI: 1.06 to >1.50%). The best-fitting models for G:F were QP, BLL, and BLQ. The QP model estimated the maximum G:F at 1.48% (95%CI: 1.23 to >1.50%), with 99% of maximum G:F achieved at 1.24%. The BLL plateau was estimated at 1.30% (95% CI: 1.18 to 1.41%), whereas the BLQ plateau was estimated at 1.36% (95%CI: 1.14 to >1.50%). In conclusion, the estimated optimum SID Lys concentration for 12- to 26-kg pigs sired by high index boars ranged from 1.30 to 1.48%, depending on the response criteria and statistical model. [Image: see text]